Investigation on futsal shoes outsole features - Shariman, I. I.; Hiroyuki, N.; Ahmad, F. S.; Solehuddin, S. (Journal of Physical Education and Sport, 2022)
This study presents the typical outsole features of futsal shoes and classifies them into several main categories. A total of 100 futsal shoes from twelve manufacturers are selected for analysis. Each shoe`s tread groove pattern, as well as other features, are visually observed. All shoes are categorised into five different groups according to their outsole features at the forefoot, mid foot and rear foot regions. The level of association between specific features and the outsole region (forefoot and rear foot) are further analysed using the chi-square test. Nine typical tread groove patterns are identified among the futsal shoes: 1. honeycomb, 2. herringbone, 3. omni, 4. waffle, 5. straight line, 6. smooth, 7. checker, 8. scribble line and 9. concentric line. Three common outsole features are identified: 1. flexi bar, 2. pivot point and 3. flex line. The results indicate that most futsal shoes (43%) are classified into Group 5 (non-identical tread groove pattern for all outsole regions). Approximately 15% of the analysed futsal shoes possess identical tread groove features (Group 4) at all three outsole regions. The pivot point and flex line are also found to be significantly associated with the forefoot region [chi2(1) = 12.05, p = .001, and chi2(1) = 4.97, p=0.026, respectively]. The variability within the outsole features of futsal shoes indicates the specific functions assigned to each region of the entire outsole. This includes the pivot point at the forefoot region, which may act as a rotational movement-assist feature, and the flex line at the forefoot region which can help optimise metatarsophalangeal joint range of motion while executing futsal-specific tasks.